2013
DOI: 10.1007/s00213-013-3307-2
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 and μ-opioid receptor antagonism blocks anticipatory 50 kHz ultrasonic vocalizations induced by palatable food cues in Wistar rats

Abstract: Rationale-Fifty kilohertz ultrasonic vocalizations (USVs) have been sometimes shown to reflect positive affective-like states in rats. Rewarding events, such as access to palatable food or drugs of abuse, increase the number of anticipatory 50 kHz USVs. However, little is known about the predictability of USVs, subtypes of USVs involved, and underlying neurobiological mechanisms.Objectives-We examined whether cue-induced anticipatory 50 kHz USVs predict palatable food intake and tested the effects of dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Consistent with this hypothesis, in dependent rats but not nondependent rats, we observed that a subset of rats that displayed high alcoholin take also had higher levels of anticipatory 50 kHz USVs compared with low-alcohol-intake rats. Previous studies have reported an increase in 50 kHz USVs in response to cues paired with appetitive stimuli, such as food [8,9], copulation [10,11], and cocaine [11,12]. Rats that had extinguished methamphetamine self-administration and then given a methamphetamine priming injection or exposed to drug-paired cues robustly emitted 50 kHz USVs and rein-stated drug-seeking behavior [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with this hypothesis, in dependent rats but not nondependent rats, we observed that a subset of rats that displayed high alcoholin take also had higher levels of anticipatory 50 kHz USVs compared with low-alcohol-intake rats. Previous studies have reported an increase in 50 kHz USVs in response to cues paired with appetitive stimuli, such as food [8,9], copulation [10,11], and cocaine [11,12]. Rats that had extinguished methamphetamine self-administration and then given a methamphetamine priming injection or exposed to drug-paired cues robustly emitted 50 kHz USVs and rein-stated drug-seeking behavior [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic vocalizations between 10 and 100 kHz were recorded and analyzed using Avisoft SASLab Pro (version 5.1, Avisoft Bioacoustics). Spectrograms were generated with a fast Fourier transform length of 512 points and overlap of 50% (FlatTop window, 100% frame size), providing a frequency resolution of 419 Hz and time resolution of 1.19 ms. Vocalizations were categorized as trill, other FM, or flat using criteria described in Buck et al [9]. Here, trill calls included the “trill FM”and “step-trill FM” categories.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as running also releases endogenous opioids [63], the calls could also reflect liking, although conflicting evidence exists whether opioid agonists or antagonists increase 50-kHz calls [64][65][66][67].…”
Section: Induction Of 50-khz Calls In Runnersmentioning
confidence: 98%